Histological and biochemical outcomes of cardiac pathology in mdx mice with dietary quercetin enrichment. Issue 1 (2nd December 2014) - Ballmann, Christopher; Hollinger, Katrin; Selsby, Joshua T.; Amin, Rajesh; Quindry, John C.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Does dietary quercetin enrichment improve biochemical and histological outcomes in hearts from mdx mice? What is the main finding and what is its importance? Biochemical and histological findings suggest that chronic quercetin feeding of mdx mice may improve mitochondrial function and attenuate tissue pathology. Patients with Duchenne muscular dystrophy suffer from cardiac pathology, which causes up to 40% of all deaths because of fibrosis and cardiac complications. Quercetin is a flavonol with anti‐inflammatory and antioxidant effects and is also an activator of peroxisome proliferator‐activated receptor γ coactivator 1α capable of antioxidant upregulation, mitochondrial biogenesis and prevention of cardiac complications. We sought to determine the extent to which dietary quercetin enrichment prevents (experiment 1) and rescues cardiac pathology (experiment 2) in mdx mice. In experiment 1, 3‐week‐old mdx mice were fed control chow (C3w6m, n = 10) or chow containing 0.2% quercetin for 6 months (Q3w6m, n = 10). In experiment 2, 3‐month‐old mdx mice were fed control chow (C3m6m, n = 10) or 0.2% chow containing 0.2% quercetin for 6 months (Q3m6m, n = 10). Hearts were excised for histological and biochemical analyses. In experiment 1, Western blot targets for mitochondrial biogenesis (cytochrome c, P = 0.007) and antioxidant expression (superoxide dismutase 2, P = 0.014) increased in Q3w6m mice compared with C3w6m. Histology revealed increased utrophin (P = 0.025) and decreased matrix metalloproteinase 9 abundance (P = 0.040) in Q3w6m mice compared with C3w6m. In experiment 2, relative (P = 0.023) and absolute heart weights (P = 0.020) decreased in Q3m6m mice compared with C3m6m. Indications of damage (Haematoxylin‐ and Eosin‐stained sections, P = 0.007) and Western blot analysis of transforming growth factor β1 (P = 0.009) were decreased in Q3m6m mice. Six months of quercetin feeding increased a mitochondrial biomarker, antioxidant protein and utrophin and decreased matrix metalloproteinase 9 in young mice. Given that these adaptations are associated with attenuated cardiac pathology and damage, the present findings may indicate that dietary quercetin enrichment attenuates dystrophic cardiac pathology, but physiological confirmation is needed.